Effects caused by a compulsive legislator in the juridical safety. The example of the amplified judicial taxes - Eduardo Sánchez Álvarez (Estudios de Deusto, 2014)
The constitutionalized juridical safety carries an own content that, simultaneously, projects especially the juridical Order to be able to qualify it, as such serving as indicative criterion of the veracious quickness of the Constitutional state. For time, it has come confi rming his material weakening, although his formal proclamation Last times have increased this constitutional suffering. In this work we propose the confirmation of this situation using an example of current importance: the new judicial taxes and their lace in the own area of the above-mentioned constitutional content. We will try to test that the result of this exercise will not be very positive. Published online: 25 November 2014